شعرية السّرد وجماليات اللّغة القصصيّة المجموعة القصصية ( الموت بالتّقسيط ) للحبيب السّائح أنموذجاً: The poetic narration and the aesthetics of the narrative language.The collection of stories (death by installments) for the tourist lover as a model - شوشان بوبكر (JAR, 2022)
This research aims to reveal the horizon of fiction writing in general and storytelling in particular , by the Algerian writer and novelist (el Habib al sayeh) through the approach of his short Story collection:(Death in Installmentsالموت بالتقسيط). writing for him opens up to a narrative Poetic , that Invests not a few possibilities and tools, in the horizon of action and movement , thought and thinking , conscious and subconsciousness and the difference between imagination and reality , memory , dream and experimentation … when carving out of the vocabulary and that is associated with it the lines of reality and the corridors of the human self… and the effectiveness of the continuous transformation in dealing with language, and transcending the prevailing mode ,in an experience that sharpens the language and creats a harmonious synthesis that that takes from different possibilities in wich the narrative , poetic and artistic mixes … , in compliance with an arthestic aesthetic that archives the uniqueness of this text on the more than one Level of knowledge.